As narrativas de mudança no contexto da economia compartilhada - Lazzari, Aline de Geroni Roncato (2019)
Sharing economy is an emerging phenomenon. From the entry of new players in the market such as Uber, Airbnb and Zipcar, further studies are carried out with the intention of understanding this which is considered as a new economy. Reviewing the literature on the subject, there is no consensus on the part of the authors regarding the origins and framing of the sharing economy. It is verified a controversy of this new economy linked to social and environmental innovation or to financial and economic aspects generating two great perspectives of argumentation in the studies. Considering the perspective of some authors, who present the possibility of understanding the sharing economy as a social perspective, and understand that the narratives are used in the construction of the social, we seek to understand the role of these narratives in the processes of transformation and social change. The purpose of this dissertation was to analyze the narratives of changes in the context of the sharing economy, and in this way we verified the approximation of the sharing economy with the social perspective. Data collection was through analysis of reports issued by recognized bodies, netnography of sharing economy initiatives, participant observation of events and interviews with managers and users of platforms. We conclude that the sharing economy presents different narratives according to the positioning when for the profit of the initiative. For-profit initiatives presented as macro-narratives "economic opportunity", "experience" and "need for specific regulation". The non-profit initiatives presented as macro-narratives "sense of community", "equity" and "transformation". Also, macro-narratives were identified that were at the intersection of the two frameworks, being "collaborative and convenience" and "sustainability". From this study, we also identify the context, actors, plot and the role of these narratives of change. It was possible to verify that the sharing economy provided some social changes as the form of access to products and services and the form of relationship between peers. Also, the form of access to income through for-profit platforms and in the specific case of non-profit initiatives the sense of community generated. This study contributes to a better understanding of the sharing economy phenomenon and its potential positive social impacts.